Design of power device sizing and integration for solar-powered aircraft application / Safyanu Bashir Danjuma, Zamri Omar and Mohd Noor Abdullah - Danjuma, Safyanu Bashir; Omar, Zamri; Abdullah, Mohd Noor (Universiti Teknologi MARA, 2021)
The power device constitutes the PV cell, rechargeable battery, and maximum power point tracker. Solar aircraft lack proper power device sizing to provide adequate energy to sustain low and high altitude and long endurance flight. This paper conducts the power device sizing and integration for solar-powered aircraft applications (Unmanned Aerial Vehicle). The solar radiation model, the aerodynamic model, the energy and mass balance model, and the adopted aircraft configuration were used to determine the power device sizing, integration, and application. The input variables were aircraft mass 3 kg, wingspan 3.2 m, chord 0.3 m, aspect ratio 11.25, solar radiation 825 W/m2 , lift coefficient 0.913, total drag coefficient 0.047, day time 12 hour, night time 12 hours, respectively. The input variables were incorporated into the MS Excel program to determine the output variables. The output variables are; the power required 10.92 W, the total electrical power 19.47 W, the total electrical energy 465.5 Wh, the daily solar energy 578.33 Wh, the solar cell area 0.62 m, the number of PV cell 32, and the number of the Rechargeable battery 74 respectively. The power device was developed with the PV cell Maxeon Gen III for high efficiency, the rechargeable battery sulfur-lithium battery for high energy density, and the Maximum power point tracker neural network algorithm for smart and efficient response. The PD sizing was validated with three existing designs. The validation results show that 20% reduction of the required number of PV cells and RB and a 30% increase in flight durations.